SOCIAL PROTECTION STRATEGIES AND HEALTH FINANCING TO SAFEGUARD REPRODUCTIVE HEALTH FOR THE POOR: MAKING A CASE FOR PAKISTAN - Shaikh, Babar Tasneem; Mazhar, Arslan; Khan, Shahzad Ali; Hafeez, Assad (Journal of Ayub Medical College Abbottabad, 2011)
Globally, a billion people cannot seek appropriate and timely healthcare because they are not covered under any social protection and health insurance system. Countries where government financing for health care is meagre, the situation is even worse. Pakistan with its slowly improving indicators of maternal and child health makes a classical case for instigating a social protection mechanism for the poor segments of population. The Government safety nets are unable to cater the large proportion of poor population. NGOs partially cover the rural areas where majority of the vulnerable population lives but need to expand their scope of work. Donors have presented variety of models and frameworks which were seldom considered in the concerned quarters. All stakeholders ought to strategise their plans to adopt and scale up the successful interventions (vouchers, cash transfers, micro-credits, community based insurance etc) which have been operating but on a very small scale or for other types of health services, but none for reproductive health care per se. Adoption of risk pooling mechanisms and provision of accessible and quality reproductive health services seems feasible through a meaningful and integrated public private partnership in the times to come. Keywords: Social protection, Health financing, Reproductive health, Health System